Testicular growth in Canchim bulls - Alencar, Maurício Mello de; Vieira, Rogério Chaves (Pesquisa Agropecuaria Brasileira, 2014)
The testicular growth of 30 Canchim bulls from weaning to 30 months of age was studied. At 30 months of age the bulls showed, on the average, 31.2 all of scrotal circumference (CE) and 171.9 cm³ of testicular volume (IVT). There was a positive relationship (P < 0.01) of CE and IVT with body weight, within age classes, indicating that the heavier the animal, the bigger are CE and IVT. CE and IVT showed a quadractic relationship (P < 0.01) with age, indicating that they increase as the animal ages, however, at a decreasing rate. The highest observed growth rate of CE was 0.0518 cm/day, from 9 to 10 months of age, occurring a linear decrease at a rate of -0.0025 cm/day/month, until reaching a rate of 0.0014 cm/day, from 27to 28 months of age. The same tendency was observed for IVT. A large variation of testicular growth was observed among bulls within the same age groups, suggesting a chance to increase testicular size by selection, since this trait, in general, shows high heritability.